2007
DOI: 10.1111/j.1475-6773.2007.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Managed Care and the Unmet Need for Mental Health Care among Children with Special Health Care Needs

Abstract: Objective. To determine the association between Medicaid managed care pediatric behavioral health programs and unmet need for mental health care among children with special health care needs (CSHCN). Data Source. The National Survey of CSHCN (2000CSHCN ( -2002, using subsets of 4,400 CSHCN with Medicaid and 1,856 CSHCN with Medicaid and emotional problems. Additional state-level sources were used. Study Design. Multilevel models investigated the association between managed care program type (carve-out, integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Multiple recent studies have failed to show differences in access for publicly and privately sponsored insurance. 11,26,29,30,32,35 On the other hand, several studies have found that CSHCN with public insurance had better access to most services, with the possible exception of mental health services, 9,25,[36][37][38][39] whereas a study by Newacheck et al 8 found that private insurance was associated with better overall access. Recent studies that examined payment mechanisms found more consistent results.…”
Section: Access To Carementioning
confidence: 96%
“…Multiple recent studies have failed to show differences in access for publicly and privately sponsored insurance. 11,26,29,30,32,35 On the other hand, several studies have found that CSHCN with public insurance had better access to most services, with the possible exception of mental health services, 9,25,[36][37][38][39] whereas a study by Newacheck et al 8 found that private insurance was associated with better overall access. Recent studies that examined payment mechanisms found more consistent results.…”
Section: Access To Carementioning
confidence: 96%
“…The resulting pattern of what constitutes the most vulnerable groups remains remarkably robust. SUN is a more serious issue for the children of the poor (the reader is referred to a systematic review of the literature on children until 2006 [22] and some later studies [23][24][25][26][27][28][29]), for the homeless [30][31][32][33], for chronically ill patients [19,20,[34][35][36], for the disabled [21,37,38], for the sick and poor elderly [39][40][41][42] and for immigrants [43]. Extending insurance coverage for these groups or strengthening social protection measures (lowering OOP payments or increasing their income) should be an obvious target for any policy aiming at improving equity of access.…”
Section: Subjective Unmet Need and Out-of-pocket Paymentsmentioning
confidence: 99%
“…7 Medicaid has played an important role in maintaining the health of children with disabilities, insuring Ïł25% of all CSHCN and covering a broad range of services that meet their complex needs. 8 Benefits of the Medicaid program include the Early and Periodic Screening, Diagnosis, and Treatment services that are mandated for categorically qualified people younger than 21 years. Mandated dental services include oral screening; preventive services including instruction in self-care for oral hygiene, cleanings, and sealants to prevent pit and fissure caries; general dental care needed for the relief of pain, infections, tooth restoration, and maintenance of dental health; and other, more advanced procedures.…”
mentioning
confidence: 99%